Efektiitas Pembelajaran Dengan Media Pembelajaran Berbasis Budaya Batak Terhadap Peningkatan Pemahaman Konsep Siswa Kelas X SMA Swasta Free Methodist Medan Pada Materi Jarak Dalam Bangun Ruang 3 Dimensi - Malau, Gideon; Sihombing, Dame Ifa; Simbolon, Lolyta Damora (Imajiner: Jurnal Matematika dan Pendidikan Matematika, 2026)
This study aims to determine the effectiveness of learning using Batak culture–based learning media in improving the mathematical conceptual understanding of Grade X students at Free Methodist Private Senior High School Medan on the topic of three-dimensional geometry. This study integrates Batak culture through the context of Jabu Bolon as a mathematics learning medium to support the visualization of distance concepts in three-dimensional geometry. In this study, local culture is not merely used as an illustrative context, but the structure and architectural form of Jabu Bolon are directly utilized as visual and contextual media in mathematics learning. The integration of local culture not only strengthens the connection between mathematical concepts and students’ real-life experiences, but also provides a more meaningful, contextual, and culturally relevant learning experience for students.This research used a quasi-experimental method with a population consisting of all Grade X students from three classes. The instruments used were tests and observations. The sample was determined through cluster random sampling, resulting in class X-C as the experimental class and class X-B as the control class. Data were collected using a conceptual understanding test. Data analysis was conducted using the Liliefors normality test, t-test, and N-Gain test. The results of the t-test showed a significance value of sig. (P(T≤t) two-tail) of 0.0074 0.05, indicating that there is a significant difference in conceptual understanding between the two sample classes. The average N-Gain score of the experimental class was 0.75 or 75%, which falls into the high category, while the control class obtained an N-Gain score of 0.39 or 39%, which falls into the medium category. When viewed from the indicators of effectiveness in the experimental class: (1) the quality of learning shows a sig. value (P(T≤t) two-tail) of 0.0074 0.05 and an N-Gain of 75%; (2) the appropriateness of the learning level is categorized as “very good” with a percentage value of 85.3%; and (3) learning time is categorized as “good” with an average score of 4.6. Therefore, it can be concluded that Batak culture–based learning is effective in improving the conceptual understanding of Grade X students on the topic of distance in three-dimensional geometry.